An ulcerated nodule on the nose. (16th April 2013) - Maybury, Catriona M; Craythorne, Emma; Martin, Blanca
Abstract : A 75-year-old retired nurse, originally from Barbados, presented to her general practitioner (GP) with a scaling ulcerated nodule on the left side of her nose. She was taking medication for type 2 diabetes, hypertension and glaucoma, but was otherwise well with no systemic symptoms. Her GP diagnosed a patch of eczema; however, a trial of topical steroids was not effective and she was referred to dermatology. A skin biopsy confirmed the clinical suspicion that this patient had a nodular basal cell carcinoma (BCC). BCCs account for 75% of all skin cancers; they very rarely metastasise, but can spread to invade local structures. Our patient has type VI skin. Skin cancer is rare in patients with skin type VI; however, in this group, morbidity and mortality are disproportionately high in relation to cancer incidence.